Early thawing after snow removal and no straw mulching accelerates organic carbon cycling in a paddy soil in Northeast China. (1st March 2018) - Zhang, Hao; Tang, Jie; Liang, Shuang; Li, Zhaoyang; Wang, Jingjing; Wang, Sining
Abstract: Variations in soil organic carbon (SOC) have implications for atmospheric CO2 concentrations and the greenhouse effect. However, the effects of snow cover and straw mulching on the variations in SOC fractions across winter remain largely unknown. In this study, soil samples were collected during different stages of winter from an in situ experiment comprising three treatments: 1) snow removal with no straw mulching (Sn-SM-); 2) snow cover with no straw mulching (SC), and; 3) snow cover with straw mulching (SC + SM+). Results showed that labile organic carbon, semi-labile organic carbon, recalcitrant organic carbon (ROC), the light fraction of organic carbon (LFOC), and easily oxidized organic carbon (EOC) contents did not vary significantly (P > .05) during the unfrozen to hard frost stages. Compared to the unfrozen stage, microbial biomass carbon (MBC) contents decreased by 519.03 mg kg −1, 325.21 mg kg −1, and 244.09 mg kg −1 and dissolved organic carbon (DOC) contents increased by 473.36 mg kg −1, 348.10 mg kg −1, and 258.89 mg kg −1 at the hard frost stage in Sn-SM-, SC, and SC + SM + treatments, respectively. Throughout all thawing stages, > 61% and 59% of SOC and ROC accumulation, respectively in the three treatments were observed in thawing stage II, indicating that higher temperatures and microbial activities in thawing stage II accelerated the inputs of SOC and ROC. ROC accumulation accounted for >65% of the SOC accumulation and the proportions of ROC in SOC increased in the three treatments during the thawing stages. SC + SM + treatment maintained lower EOC contents during thawing stages than other treatments. The observation of lowest SOC and LFOC accumulation and contents in the SC + SM + treatment during thawing stages showed that SC + SM + experienced the least inputs of SOC in the soil. Highlights: Variations of soil organic carbon and its fractions are revealed during winter. Straw mulching and snow cover reduce the microbial biomass loss and the DOC release during freezing to hard frost stages. Snow cover and straw mulching facilitated the inhibition of the decomposition of residues during thawing stages. Snow cover and straw mulching help alleviate the mineralization of soil organic carbon. Recalcitrant organic carbon accumulation dominates soil organic carbon storage during thawing stages.